2009
DOI: 10.1515/semi.2009.029
|View full text |Cite
|
Sign up to set email alerts
|

The semiosis of stone: A “rocky” rereading of Samuel Taylor Coleridge through Charles Sanders Peirce

Abstract: We present several existential-like graphs and models of the ontological links found along a continuum from physiosemiosis to anthroposemiosis. Our models derive from our rereading of Samuel Taylor Coleridge's theories of the symbol and of his notion of the ''outness'' of mind in terms of Charles Sanders Peirce's ''semeiotic,'' a rereading by which we introduce an ecocritical and pansemiotic mode of literary ecology called Renewable Historicism and argue for a new, distributed understanding of intentionality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…On the other hand, we turn to Peirce's semeiotic for a categorization of Austin's examples of pretending as well as an answer to the two questions at issue. Inspired from recent works by semiotic scholars like Coletta et al (2009), Pearson (2008), Danesi (2004), Haworth and Prewitt (1998), Hausman (1993), etc., we have found that the topic of pretending and its meaningful prob lems can be placed in "the new science of semiotics" for a new understanding of the dynamic relation of human language to the signing actions of nature. Accord ingly, when we ask what is "pretending to pretend," we have to know how to measure pretending.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we turn to Peirce's semeiotic for a categorization of Austin's examples of pretending as well as an answer to the two questions at issue. Inspired from recent works by semiotic scholars like Coletta et al (2009), Pearson (2008), Danesi (2004), Haworth and Prewitt (1998), Hausman (1993), etc., we have found that the topic of pretending and its meaningful prob lems can be placed in "the new science of semiotics" for a new understanding of the dynamic relation of human language to the signing actions of nature. Accord ingly, when we ask what is "pretending to pretend," we have to know how to measure pretending.…”
Section: Introductionmentioning
confidence: 99%
“…Icons can be divided into subtypes based on their level of mediation and conventionality, and this is why they can serve as a powerful analytical device in a discussion about the diversity of biological mimicry. Semiotics has also proven its usefulness in analyses of the foundations or basis of resemblance (Sonesson 2010), truth conditions, types of references involved in mimicry (Coletta et al 2009;El-Hani et al 2010), and in the interpretations of the fuzzy resemblances present in abstract mimicry (Maran 2017) and in mimicry rings (Kleisner and Markoš 2005;Kleisner 2015). By focusing on the formal aspects of mimicry systems and the functions of the different participants (including human observers), semiotics can help biology to better understand nature's diverse forms of mimicry.…”
mentioning
confidence: 99%